Fragmentation and connectivity considerations for Larimer County open space lands - Decker, Karin, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2018)
Recreational use of Horsetooth Mountain Open Space and other open space properties is also increasing concern about the effects of habitat fragmentation, and county staff are in need of information about methods of retaining connectivity in these areas. This report summarizes a literature review of existing methods for identifying and managing fragmentation and maintaining functional habitat patches, with a focus on foothill habitat types that are present in Larimer County.
Keywords: conservation planning